Caseload management and outcome of patients with aortic stenosis in primary/secondary versus tertiary care settings—design of the IMPULSE enhanced registry. Issue 2 (21st July 2019) - Rudolph, Tanja K.; Messika-Zeitoun, David; Frey, Norbert; Lutz, Matthias; Krapf, Laura; Passefort, Stephanie; Fryearson, John; Simpson, Helen; Mortensen, Kai; Rehse, Sebastian; Tiroke, Andreas; Dodos, Fotini; et al.
Abstract : Background: Severe aortic stenosis (AS) is one of the most common and most serious valve diseases. Without timely intervention with surgical aortic valve replacement or transcatheter aortic valve replacement, patients have an estimated survival of 2–3 years. Guidelines for the treatment of AS have been developed, but studies suggest that as many as 42% of patients with AS are not treated according to these recommendations. The aims of this registry are to delineate the caseload of patients with AS, outline the management of these patients and determine appropriateness of treatments in participating centres with and without onsite access to surgery and percutaneous treatments. Methods/design: The IMPULSE enhanced registry is an international, multicentre, prospective, observational cohort registry conducted at four central full access centres (tertiary care hospitals) and at least two satellite centres per hub (primary/secondary care hospitals). An estimated 800 patients will be enrolled in the registry and patient follow-up will last for 12 months. Discussion: In addition to the primary aims determining the caseload management and outcome of patients with AS in primary, secondary and tertiary care settings, the registry will also determine a time course for the transition from asymptomatic to symptomatic status and the diagnostic steps, treatment decisions and the identification of decision-makers in tertiary versus primary/secondary care hospitals. The last patient will be enrolled in the registry in 2018 and results of the registry are anticipated in 2019. Registration number: NCT03112629 .